DIALECTICS OF THE EMERGENCE OF A CIVIL SOCIETY AND STATE SUPPORT OF NGOS IN TAJIKISTAN - KARIMOV, Shamsiddin (CENTRAL ASIA AND THE CAUCASUS, 2006)
A civil society and democracy in Tajikistan are being cultivated on local soil—they are not “alien transplants.” The republic is ready to embrace the great transformation already going on, and the new phenomena have not weakened society’s immunity: we are all eyewitnesses to the birth of a new statehood and stronger national identity that will determine cultural development in the broadest sense of the word. But we must keep in mind that cultural development is impossible without mutual integration of this new statehood and stronger national identity in the spirit of genuine democratization. However, from the dialectical viewpoint, the process is far from simple: a civil society ruled by law is coming into being by way of many contradictions, difficulties, meandering, and backtracking. As the road leading to a civil society ruled by law, democratization can be visualized as the sum total of numerous development vectors: some of them at times slow down the process, while others tend to miss certain seemingly logical stages by speeding things up. Talking of speeding up, it should be noted that Tajikistan, as a country at the crossroads between the secular and Oriental religion-intensive civilizations, has moved a long way along one of the vectors of the dialectical continuum. I have in mind the fact that a party of political Islam is functioning successfully in the legal context and is equally successfully integrating into the country’s legal field. This part of the dialectics of the emergence of a civil society ruled by law has far outstripped all similar processes taking place in similar spheres in Tajikistan’s Central Asian neighbors. There is the opinion that political parties do not belong to a civil society, yet the Islamic Revival Party of Tajikistan is not limited to its party structure—its impact on the civil consciousness sector and NGOs that represent the structures and norms of civil society is obvious and tangible. On the other hand, the establishment and functioning of the institution of ombudsman as a civil society phenomenon present in the Central Asian states (which are not considered democratic enough), but absent in Tajikistan, speak of the erratic nature of the process’s manifestations in the country. There is an ideological-psychological barrier of sorts that interferes with the acceptance of democratic norms and civil society’s constructive democratic opposition to the state’s spreading influence. This is caused by the emergence of a new statehood in Tajikistan, a process that is still underway, and the specific conditions of the current development stage, which is sometimes described as a “concentration of power.” The barrier can be overcome; to do this we should first fill the vacuum in the consciousness of society and the entities of public and political action with the realization that a civil society and NGOs are the key factors in the sphere of democracy. We should cultivate the idea that pluralism—political and non-political alike—is the cornerstone of democratization in the nation’s life.